2021
DOI: 10.37992/2021.1203.133
|View full text |Cite
|
Sign up to set email alerts
|

Trait relationship and path analysis under sodicity in Nagina 22 rice mutants

Abstract: The present study was conducted for evaluating EMS induced mutants for sodicity tolerance in rice. A set of 402 Nagina 22 rice mutants along with three sodicity tolerant check varieties namely TRY2, TRY3 and TRY4 were screened at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
3
2
0
Order By: Relevance
“…Single plant yield exhibited significant and positive correlation with PH, NT, NPT, FLL, PL, FPP, PW and HGW under sodicity. These results were in accordance with Sharma et al (2022) for PH and NPT, Rajasekar et al (2021) for NT, NPT, FLL, PW and HGW and Shrivastav et al (2020) for PL and FPP. On the other hand, SS exhibited negative and significant correlation with SPY.…”
Section: Sodicitysupporting
confidence: 91%
See 1 more Smart Citation
“…Single plant yield exhibited significant and positive correlation with PH, NT, NPT, FLL, PL, FPP, PW and HGW under sodicity. These results were in accordance with Sharma et al (2022) for PH and NPT, Rajasekar et al (2021) for NT, NPT, FLL, PW and HGW and Shrivastav et al (2020) for PL and FPP. On the other hand, SS exhibited negative and significant correlation with SPY.…”
Section: Sodicitysupporting
confidence: 91%
“…Path analysis under sodicity revealed positive and highest direct effect of PL towards SPY followed by NPT, FPP, HGW and PW. Similar higher direct effects of NPT, HGW and PW were reported by Rajasekar et al (2021) and of NPT, PL and FPP were reported by Singh et al (2022). The indirect effects of some traits also had higher effects on SPY.…”
Section: Sodicitysupporting
confidence: 75%
“…In this study, path coefficient analysis revealed that % survival, Na + concentration, K + concentration and Na + /K + ratio are the major traits to contribute salt tolerance because these variables jointly explain a major phenotypic variation. Many researchers also made similar observations [5,9,38]. This study is strongly supported by those researchers.…”
Section: Assessing the Salt-stress Responses In The Selected F2:3 Pro...supporting
confidence: 86%
“…Hitherto, 11 genotypes, RG113, RG22, RG150, RG162, RG188, RG26, RG50, RG95, RG107, RG123 and RG176, with significant yield coupled with sodicity tolerance may be used as a donor for breeding rice varieties tolerant to salt stress. A similar approach has been followed by Rajasekar et al (2021) in which useful rice mutants were identified based on simultaneous screening under hydroponics and field.…”
Section: Resultsmentioning
confidence: 99%
“…The seedlings were raised in Yoshida medium for the first 3 days followed by screening for sodicity with the addition of 100 mM NaHCO 3 in the same medium. Earlier, Rajasekar et al (2021) found that 50 per cent mortality of rice genotypes occurs at 100 mM NaHCO 3 and the same has been fixed as screening for sodicity.…”
Section: Methodsmentioning
confidence: 99%